Wear of lead free copper alloy-graphite particle composite - Nath D.; Prasad N.; Rohatgi P.K. (My University, 2025)
Copper alloy-graphite particle composite (60Cu - 37.5Zn, 1.75 Graphite, 0.75Ti) was developed as a substitute for leaded copper alloy used in plumbings and bearings and wear tested under cast and extruded conditions. The wear volume and rate were determined as a function of sliding distance and load. Optical and Scanning Electron Microscopy was used to study the wear debris and worn surfaces respectively. The wear volume and rate of the composite increased with increasing load and sliding distance and was comparable to those of leaded copper alloy (60Cu -37.5Zn, 1.75Pb, 0.75Sn) at higher loads. The size of wear debris decreased with increasing load. SEM studies indicated adhesive wear to operate.